Consumption and biochemical impact of commercially available plant-derived nutritional supplements. An observational pilot-study on recreational athletes - Borrione Paolo; Rizzo Marta; Quaranta Federico; Ciminelli Emanuela; Fagnani Federica; Parisi Attilio; Pigozzi Fabio (Taylor & Francis Group, 2012)
Abstract Background A growing consumption of natural (plant-derived) dietary supplements with ergogenic aims, with particular regard for ecdysteroids, phytoestrogens and vegetal sterols, has been registered over the last years among "recreational" athletes. The present study was carried out in order to evaluate the real knowledge of plant-derived nutritional supplements among physically active people as well as their real consumption. Additional aim was to evaluate the effects of these supplements on the health profile of the users. Methods Twenty-three trained subjects who habitually used natural dietary supplements, and 30 matched controls were analyzed for plasma biochemical markers and hormonal profile. Results The laboratory tests revealed the absence of any sign of organ toxicity/damage in both athletes and controls. On the contrary, hormone profiles revealed marked alterations in 15 (65%) out of the 23 of investigated athletes. Specifically, 10 males presented increased plasma levels of progesterone, 15 subjects presented abnormal estrogen levels, including 5 (2 F and 3 M) presenting a "dramatic" increased estrogen values and 2 two males with increased estrogen levels, increased testosterone levels and associated suppression of luteinizing hormone and follicle-stimulating hormone. Conclusions The results of the present study highlighted that the habitual consumption of plant-derived nutritional supplements is frequently associated with significant hormonal alterations both in male and female subjects. Although these biochemical alterations were not associated with signs or symptoms of organ toxicity/damage at the moment of the study, it cannot be excluded that, in the mid/long-term, these subjects would suffer of health problems secondary to chronic exposure to heavily altered hormonal levels. Further large scale studies are needed to confirm the results of this pilot study as well as to investigate the biological mechanisms at the base of the observed hormonal alterations.